Desain Pemberitaan Injil Berbasis Pengenalan Budaya Suku Jawa (Studi Kasus Keluarga Suk di Surakarta) - Soleman Kawangmani (Sekolah Tinggi Teologi Kalimantan, 2021)
The preaching of the gospel is always dealing with the culture of the listener. The introduction of culture and its use as a communication bridge will make the preaching of the gospel more effectively. On the other hand, cultural neglect can lead to rejection or acceptance and a syncretic living of the gospel. The purpose of this study is to find a design for preaching the gospel based on the introduction of Javanese family culture. This research uses a qualitative approach with a case study method. Collecting data through in-depth interviews and observations of the Javanese Suk family in Surakarta and literature study. The researcher found the worldview of the Suk family as the core of culture, namely animism. To reach Javanese families with animistic religious orientation with the Bible, the researcher proposes a “Gospel Preaching Design-6P”, consisting of six components, namely preparation of evangelists; 'desire for salvation, happy and peaceful life as a point of contact with the Gospel and culture, phasing out the contents of the gospel message, carrying out the preaching of the gospel, the importance of love motivation, prayer and the help of the Holy Spirit, as well as corrective discipleship as the basis for continued ministry. These six design components must be integrated into their implementation.Pemberitaan Injil selalu berhadapan dengan budaya pendengar. Pengenalan budaya dan pemanfaatannya sebagai jembatan komunikasi akan mengefektifkan pemberitaan Injil. Sebaliknya, pengabaian budaya dapat mengakibatkan penolakan atau penerimaan dan penghayatan Injil yang sinkretis. Tujuan penelitian ini yaitu menemukan suatu desain pemberitaan Injil berbasis pengenalan budaya rumpun keluarga bersuku Jawa. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus. Pengumpulan data melalui wawancara mendalam dan pengataman kepada keluarga Suk yang bersuku Jawa di Surakarta dan studi pustaka. Peneliti menemukan worldview keluarga Suk sebagai inti budaya yaitu animisme. Untuk menjangkau keluarga suku Jawa berorientasi keagamaan animisme dengan Injil, peneliti mengusulkan suatu “Desain Pemberitaan Injil-6P”, terdiri dari enam komponen yaitu persiapan penginjil; ‘dambaan keselamatan, hidup bahagia dan tenteram’ sebagai point of contact Injil dan budaya, pentahapan isi berita Injil, pelaksanaan pemberitaan Injil, pentingnya motivasi kasih, doa dan pertolongan Roh Kudus, serta pemuridan korektif sebagai basis pelayanan lanjutan. Keenam komponen desain ini harus diintegrasikan dalam pelaksanaannya.